Effects of Alhagi maurorum Medik polysaccharide derived from different regions on the intestinal immune functions of lambs - Manafu, Zulikeyan; Du, Ronglijiao; Malajiang, Xieraili; Abulikemu, Gulimire; Xue, Lijun; Bierdelieke, Ayibike; Xie, Yuan; Liu, Dandan; Mai, Zhanhai; Guo, Qingyong; Wusiman, Adelijiang; Li, Bin; et al. (Frontiers in Pharmacology, 2024)
Ficus carica L. polysaccharides (FLP) are groups of biologically active metabolites extracted from the of the Ficus carica L. In this study, we analyzed the structure of FLP and investigated their effects on growth performance, slaughter performance, immunoglobulin levels, cytokines, cecal short-chain fatty acids (SCFAs) and microbial community structure in broiler chickens. The results showed that FLP are comprised of monosaccharides like rhamnose, arabinose, mannose, glucose and galactose. Feeding high-dose FLP significantly promoted the actual body weight (ABW), average daily weight gain (ADWG) and average daily food intake (ADFI), significantly reduced the feed weight gain ratio (F/G), and promoted multiple indicators of slaughter performance and meat quality of broilers (P <0.05). Moreover, supplementation of FLP-h increased the levels of immunoglobulins (sIgA and IgG), cytokines (IL-4, IL-5, IL-12 and IFN-γ), percentage of CD3e + , CD4 + and CD8a + T-cells and levels of various SCFAs as compared to the control group (P < 0.05). Additionally, FLP also improves the abundance of beneficial bacteria such as Firmicutes and Bacteroidetes at the phylum level, and Faecalibacterium, Blautia, Phascolarctobacterium, and Alistipes at the genus level. These results suggest that dietary supplementation with FLP-h effectively promotes growth performance, slaughtering performance, strengthens intestinal immunity, and positively influences the intestinal microbiota in broiler chickens. These findings highlight the importance and potential use of FLP as a novel immunomodulator and feed additives.